Efficient Approaches to the Mixture Distance Problem - Justie Su-Tzu Juan; Yi-Ching Chen; Chen-Hui Lin; Shu-Chuan Chen (Algorithms, 2020)
The ancestral mixture model, an important model building a hierarchical tree from high dimensional binary sequences, was proposed by Chen and Lindsay in 2006. As a phylogenetic tree (or evolutionary tree), a mixture tree created from ancestral mixture models, involves the inferred evolutionary relationships among various biological species. Moreover, it contains the information of time when the species mutates. The tree comparison metric, an essential issue in bioinformatics, is used to measure the similarity between trees. To our knowledge, however, the approach to the comparison between two mixture trees is still unknown. In this paper, we propose a new metric named the mixture distance metric, to measure the similarity of two mixture trees. It uniquely considers the factor of evolutionary times between trees. If we convert the mixture tree that contains the information of mutation time of each internal node into a weighted tree, the mixture distance metric is very close to the weighted path difference distance metric. Since the converted mixture tree forms a special weighted tree, we were able to design a more efficient algorithm to calculate this new metric. Therefore, we developed two algorithms to compute the mixture distance between two mixture trees. One requires <semantics>O(n2)</semantics> and the other requires <semantics>O(nh1h2)</semantics> computational time with <semantics>O(n)</semantics> preprocessing time, where n denotes the number of leaves in the two mixture trees, and <semantics>h1</semantics> and <semantics>h2</semantics> denote the heights of these two trees.